Wings on wheels: A feasibility study on establishing a flavored chicken wings food truck in Intramuros, Manila - Abueg, Rocellia V., Flores, Jackie Lou D., Galvan, Roschack V., Gustillo, Merylle Shayne B., Macasling, KC P., Magno, Matthew., Nicerio, Maria Jesusa., Occupado, Paulino S., Sang-olan Lady Angelika B., Vergara, Kimberly Joy F. 4 0 16; 5
u
Feasibility Study: (BSBA major in Marketing Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2